2020
DOI: 10.3390/en13051136
|View full text |Cite
|
Sign up to set email alerts
|

How Much Energy Efficient are Renewable Energy Sources Cooperatives’ Initiatives?

Abstract: In this paper is provided a systematic, in-depth, behavioral analysis of renewable energy sources cooperatives' members. The analysis proved that in, on hand, there was a noticeable difference in the portion of affection of each proposed intervention on the actual energy consumption, which may be to even ten times more in some cases, and on the other hand, the difference in energy consumption between the analyzed groups was noticeable as well. So, implementing energy efficiency interventions of various types, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The energy consumption data obtained from the REScoops allowed conducting longitudinal time series trend analysis that revealed several important findings (Sifakis et al, 2018(Sifakis et al, , 2019. The key finding is that implementing energy efficiency interventions of various types, such as technical support, special tariffs, energy generation schemes, and smart meters, leads to substantial energy reductions of more than 10%, cumulatively (Sifakis et al, 2020). More specifically, joining a REScoop was found to lead to a more than 20% reduction in electricity consumption.…”
Section: Results From the Rescoop Plus Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy consumption data obtained from the REScoops allowed conducting longitudinal time series trend analysis that revealed several important findings (Sifakis et al, 2018(Sifakis et al, , 2019. The key finding is that implementing energy efficiency interventions of various types, such as technical support, special tariffs, energy generation schemes, and smart meters, leads to substantial energy reductions of more than 10%, cumulatively (Sifakis et al, 2020). More specifically, joining a REScoop was found to lead to a more than 20% reduction in electricity consumption.…”
Section: Results From the Rescoop Plus Projectmentioning
confidence: 99%
“…Due to the availability of data, actual consumption data focused on electricity consumption (excluding gas and other sources needed for heating of homes and tap water). Next to longitudinal data sets additional data were obtained from REScoops (or companies performing energy service management to REScoops) about members and non-members clients (consuming energy supplied by REScoops, or persons otherwise connected as non-clients) to the REScoop community about their energy use (Sifakis et al, 2018(Sifakis et al, , 2020.…”
Section: Methodsmentioning
confidence: 99%
“…These in particular concern the Dr. Watt program, Smart Meter installation, and EnergieID and InfoEnergia. Energy communities encouraging their members to install solar panels and become 'prosumers' was also found to have an impact (Sifakis et al, 2020). Moreover, the in-depth case study revealed that using energy ambassadors and local energy front offices ('energieloket' in Dutch) also seems to work effectively as they are well-practiced in this work and are valued by different stakeholders (Schwencke, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Longitudinal time series trend analysis revealed a number of important findings (Sifakis et al, 2018). The key finding is that implementing energy efficiency interventions of various types, such as technical support, special tariffs, energy generation schemes and smart meters, leads to substantial energy reductions of more than 10 per cent, cumulatively (Sifakis et al, 2020). More specifically, joining a REScoop was found to lead to a more than 20 per cent reduction in electricity consumption.…”
Section: Effects Of Dedicated Energy Saving Measures Implemented By E...mentioning
confidence: 99%
See 1 more Smart Citation